Biomass and Carbon Stock in the Sal (Shorea robusta) Forest of Dang District Nepal - Supuspa Regmi; Krishna Prasad Dahal; Garima Sharma; Siddhartha Regmi; Mahamad Sayab Miya (Indonesian Journal of Social and Environmental Issues (IJSEI), 2021)
The study was conducted to find the net carbon stock in the Sal (Shorea robusta) forest in Bagdaila Chisapani community forest of Dang district, Nepal. The inventory was done by a stratified sampling technique with 0.5% sampling intensity taking into account the woody plants with ≥ 5cm DBH. A total of 49 sample plots of radius 8.94m and 5.64 were established to measure tree biomass and sapling biomass respectively in the forest. The mean above-ground carbon (AGC) was 160.4 t ha-1 and the mean below-ground carbon (BGC) was 24.1t ha-1. The mean total carbon stock in the study area was estimated to be 99.02 t ha-1; of which maximum carbon stock of 143.51 t ha-1 was found in block number 5. Sal was the major tree species in the CF. The biomass and carbon content in this forest is found quite low as compared to other studies in the Sal forest and other tropical forests which were due to the presence of tree stands of less diameter and height. This study would be helpful in the long-term management of forests, planning, and research purposes. The data from this study could also be taken as a reference document for the participation of community forests in carbon accounting under the REDD+ scheme in Nepal.